Assessing the Variability of Antibiotic Management in Patients With Open Hand Fractures Presenting to the Pediatric Emergency Department. Issue 10 (27th October 2022) - Görgens, Sophia; Patel, Deepa; Keenan, Kaitlin; Fishbein, Joanna; Bullaro, Francesca
Abstract : Objectives: Open hand fractures may be difficult to recognize and treat. There is variability in management and administration of antibiotics for these types of injuries. Unlike open long bone fractures, there is no standardized protocol for antibiotic administration for open hand fractures in children. The objective of this study is to assess the variability of antibiotic management of open hand fractures in children. Methods: We performed a retrospective chart review at a tertiary hospital in New York of patients with hand injuries between ages 0 and 18 years presenting to the emergency department during January 2019 and December 2020. Patient encounters were reviewed for open fractures of the hand. Descriptive statistics were included for demographic and physical characteristics. Results: There were 80 encounters with open hand fractures, of which the most common being tuft fractures (77.5%). The mean age was 7.6 years (SD, 4.7 years) with male predominance (58.8%). Crush injuries were the most common mechanism of injury (78.8%). Bedside repair was performed on 62 encounters (77.5%), of which 45 (72.5%) required nail bed repair, 56 (90.3%) required suturing, and 24 (38.7%) required reduction. Antibiotics were given to 62 (77.5%) encounters, most commonly oral cefalexin (45.2%), oral amoxicillin-clavulanic acid (27.4%), and intravenous cefazolin (14.5%). Median time to antibiotics from emergency department registration to administration was 150 minutes (interquartile range, 92–216 minutes). Antibiotic prescriptions were sent for 71 encounters (88.8%). Seventy seven (96.3%) of the encounters were discharged home. Conclusions: Pediatric open hand fractures have a variability of type and timing to antibiotics. Future initiatives should attempt to create standardized guidelines for management of open hand fractures.